An Infusion Monitoring System With An Internet Of Things Based On Smartphone - Naurah Nazhifah; Yohandri Yohandri (Journal of Experimental and Applied Physics, 2025)
Infusion is one of the most frequently used medical mechanisms as a therapeutic. The volume of infusion fluid, when not monitored regularly, can harm the patient. When the infusion fluid has run out and is not immediately replaced, the air will enter the blood vessels. Infusion monitoring in Indonesia is still done manually. Previous research has developed an infusion monitoring device using Arduino however, this device generally lacks remote monitoring capabilities, thus tending to use microcontrollers inefficiently. To address these issues, an Infusion monitoring system was designed using the NodeMCU ESP8266. This device reads the number of infusion fluid drops using an Optocoupler sensor, and a Load cell sensor measures the percentage of remaining fluid. Measurement results can be detected easily and quickly via a smartphone. The innovation in this system lies in the Internet of Things (IoT), which enables remote control. The research conducted was to determine the design specifications and performance specifications of the device. This can be seen from the results of the device design specifications, namely the average accuracy of the infusion rate of the number of drops/minute is 98.89% with an average accuracy of 98%, while the average accuracy of the remaining infusion fluid percentage is 96.8% with an average accuracy of 98%. This system offers an efficient and controlled solution for combining infusion fluids. By integrating IoT technology, this research paves the way for the development of more advanced infusion monitoring systems, supporting improved patient care in the era of global healthcare